Youth soccer players, 11-14 years: Maturity, size, function, skill and goal orientation - Figueiredo, António J. (2009)
Background: Participants in many youth sports are commonly combined into age groups spanning 2 years. Aim: The study compared variation in size, function, sport-specific skill and goal orientation associated with differences in biological maturity status of youth soccer players within two competitive age groups. Methods: The sample included 159 male soccer players in two competitive age groups, 11-12 years (n=87) and 13-14 years (n=72). Weight, height, sitting height and four skinfolds, four functional capacities, four soccer skills and goal orientation were measured. Skeletal maturity was assessed using the Fels method. Each player was classified as late, on time or early maturing based on the difference between skeletal and chronological ages. ANOVA was used to compare characteristics of players across maturity groups. Results: Late, on time and early maturing boys are represented among 11-12-year-olds, but late maturing boys are under-represented among 13-14-year-olds. Players in each age group advanced in maturity are taller and heavier than those on time and late in skeletal maturity, but players of contrasting maturity status do not differ, with few exceptions, in functional capacities, soccer-specific skills and goal orientation. Conclusion: Variation in body size associated with maturity status in youth soccer players is similar to that for adolescent males in general, but soccer players who vary in maturity status do not differ in functional capacities, soccer-specific skills and goal orientation.